Analysing Impactful Slogans in WHO’s Immunisation Campaigns: Study on Linguistic Strategies for Promoting Vaccination - Skorupa, Pavel; Stunžaitė, Alisa; Dubovičienė, Tatjana (Respectus Philologicus, 2024)
Utilising the content and discourse analyses, the article aims to reveal the shared rhetorical linguistic tactics employed in 16 slogans from WHO’s Immunisation Week campaigns (2013–2023) to proficiently communicate messages. Slogans are vital for promoting vaccination in public health initiatives. The analysis reveals graphical, phonological, lexical, syntactic, and semantic features of slogans. Graphically, partial capitalisation and hashtags enhance visibility and engagement. Phonological features include alliteration and assonance, creating memorable rhythms. Lexically, inclusive language and action verbs motivate and persuade. Syntactically, imperative verbs, parallel structures, repetitions, and ellipses enhance impact and memorability. Semantically, puns, personifications, metaphors, and antitheses add depth and engage the audience. The findings inform future campaigns, facilitating the development of impactful slogans to combat vaccine-preventable diseases.
Keywords: slogans; WHO immunization campaign; vaccination; linguistic strategies; advertising